Phylogenetic relationships and biogeography of Ptilophora (Gelidiales, Rhodophyta) with descriptions of P. aureolusa, P. malagasya, and P. spongiophila from Madagascar. Issue 2 (2nd February 2018) - Boo, Ga Hun; Gall, Line Le; Hwang, Il Ki; Miller, Kathy Ann; Boo, Sung Min
Abstract : The genus Ptilophora currently includes 16 species occurring mostly in subtidal habitats of the Indo‐Pacific Ocean, but its global diversity and biogeography are poorly understood. We analyzed mitochondrial cox 1, plastid rbc L and plastid psb A sequences from specimens collected in southern Madagascar during the 2010 Atimo Vatae expedition and studied their morphologies. Both morphological and molecular data sets demonstrated the presence of five species in southern Madagascar: Ptilophora hildebrandtii, P. pterocladioides, and three new species described here, P. aureolusa, P. malagasya, and P. spongiophila . Ptilophora aureolusa is distinguished by its compound pinnae with uniformly spaced pinnules. Ptilophora malagasya has an indistinct midrib and irregularly spaced pinnules. Ptilophora spongiophila, heavily coated with sponges, has cylindrical to flattened main axes, lateral and surface proliferations, and spatulate tetrasporangial sori. The species of Ptilophora found in Madagascar are endemic, except P. hildebrandtii, which also occurs in eastern Africa. Ptilophora comprises four phylogenetic groups that map to eastern Australia, Japan, western Australia/Southeast Asia/Madagascar/eastern Africa, and Madagascar/eastern Africa/Aegean Sea. Biogeographical analysis revealed that the ancestor of Ptilophora originated in Australia, but most of the species radiated from Madagascar.